On the issue of classification of Mallory-Weiss syndrome (Eurasian Medical Research Periodical, 2024)
The aim of the study was to improve the treatment outcomes of patients with MalloryWeiss syndrome by systematizing the clinical signs of the disease and a differentiated approach to the choice of treatment method